2019
DOI: 10.33395/owner.v3i2.159
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kualitas Produk, Citra Merk dan Promosi terhadap Keputusan Pembelian Spare part pada Bengkel Aneka Motor Kabupatan Padang Pariaman

Abstract: This study aims to determine how much influence the variable quality of the product, brand image and promotions simultaneously and partially on purchasing decisions motorcycle spare parts in the garage Aneka Motor Padang Pariaman. By using the method of data collection in the form of the questionnaire and the analysis method used is multiple linear regression analysis. The result showed that the variable quality of the product, brand image, and promotions significantly influence the purchasing decisions of spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Customers really want friendly service quality, supported by affordable product prices and attractive promotions about products. In line with this statement, research conducted by (Rustam, 2019) found that promotion has a positive influence on customer decisions in making purchases. Furthermore, research conducted by (Kurniawan, 2016;Margaretha, 2012) stated that price and service quality are factors that affect purchasing decisions.…”
Section: Monthmentioning
confidence: 59%
See 2 more Smart Citations
“…Customers really want friendly service quality, supported by affordable product prices and attractive promotions about products. In line with this statement, research conducted by (Rustam, 2019) found that promotion has a positive influence on customer decisions in making purchases. Furthermore, research conducted by (Kurniawan, 2016;Margaretha, 2012) stated that price and service quality are factors that affect purchasing decisions.…”
Section: Monthmentioning
confidence: 59%
“…The Indonesian Motorcycle Industry Association recorded motorcycle sales in 2019 reaching 6,487,430 units, with details of Honda contributing sales of 4,910,688 units or 75,69%, Yamaha with sales of 1,434,217 units or 22,1%, Suzuki with total sales of 71,861 units or 1,1%, Kawasaki with sales of 69,766 units or 1.08%, TVS with sales of 898 or 0,01%. This makes Honda the most popular motorcycle brand in Indonesia (Rustam, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has not sparked consumer interest. From the results, promotion is an activity to influence consumers to become familiar with the company's products and then become happy and then buy the product (Petricia & Syahputra, 2015;Rustam, 2019). The recommendations offered based on the findings of this study are to improve product quality, such as waste and responsive performance.…”
Section: Modelmentioning
confidence: 94%
“…A company has a variety of activities in its company, not only making a product or service but also marketing it by telling about the benefits, advantages of the product, and the advantages of the product. In the activity of marketing a product, there are several promotions (Petricia & Syahputra, 2015;Rustam, 2019;Santosa, 2019).…”
Section: Introductionmentioning
confidence: 99%